Peran TNI AD dalam Proses Pelaksanaan Pemilihan Umum Tahun 2024 - Anton (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2023)
Indonesia is a democratic country where one of the democratic practices carried out by Indonesia is by voting to determine future leaders. Elections are a means in the process of implementing people's sovereignty which is carried out directly, publicly, freely, confidentially, honestly and fairly which applies in a unitary state of the Republic of Indonesia which is based on Pancasila and the 1945 Constitution. In the process of writing this research the author uses a design library research or what is called a literature review where the sources obtained by the author come from references and foundations from previous research, apart from that the author also uses library research methods where the sources obtained by the author come from books, articles and other sources. Based on this method, the author has determined the problem formulation in this journal, namely (1) the role of the TNI AD in the process of implementing the 2024 general election, (2) Prohibitions for TNI soldiers during the election, (3) Consequences for TNI members who are caught committing election violations. And the conclusions from writing this journal are (1) the TNI AD plays a very important role in maintaining security and order in Indonesia during this democratic party, guarding the election so that it is safe and peaceful, the professionalism of the TNI in carrying out election security and participating in conducting outreach to the public so that they can participating in the election, (2) the prohibition for a member of the TNI in carrying out the election is a prohibition on providing comments, assessments and directions relating to the election to the family and also the community, a prohibition for individuals to be at the location where the election is held, ( 3) prohibition on displaying banners, billboards and campaign attributes that describe the identity of election participants, prohibition from being in the voting area, prohibition against interfering in and influencing KPU decisions and prohibition against becoming members of the KPU, Panwaslu and so on. (3) If during the election a member is found to have committed a violation, he or she will be subject to sanctions and consequences in the form of a criminal penalty of one year in prison and a fine of up to RP. 12,000,000 if proven to have violated the prohibition against a member of the TNI. TNI members do not have the right to vote and must be neutral in the implementation of the simultaneous elections which will be held on February 14 2024.